Gender-inclusive sexual health literacy scale for sex workers (SHL-SW): Development and validation in Thailand - Saowanee Thongnopakun; Worarat Magteppong; Sawitree Visanuyothin; Jaturapon Charoenying; Orathai Thongnoppakun; Pitak Ketkrongkuay; Natsariya Chaksomsak; Aimutcha Wattanaburanon; Yuvadee Rodjarkpai; Tanunchai Boonnuk (PLoS ONE, 2026)
Background Marginalized sex workers worldwide face persistent sexual health inequities, yet lack a validated, gender-inclusive tool to measure their sexual health literacy (SHL). This study aimed to develop and validate the Gender-inclusive Sexual Health Literacy Scale for Sex Workers (SHL-SW). Methods A mixed methods approach was employed in three stages: (1) literature review, (2) expert consultation using the Delphi technique, and (3) questionnaire development and validation. The participants included 18 experts, 5 competent evaluators, and 600 sex workers. Data were collected through interviewer-administered online questionnaires. Analyses methods included median, interquartile range, content validity index, Cronbach’s alpha coefficient, and confirmatory factor analysis (CFA). Results The final 10-item SHL-SW demonstrated high internal consistency (Cronbach’s α = 0.92). The CFA confirmed the hypothesized four-factor structure (access, understanding, appraisal, and application), with model fit indices indicating an excellent fit to the data (χ² = 20.568, p = 0.151; CFI = 0.99; TLI = 0.98; RMSEA = 0.04; SRMR = 0.03), thus establishing strong construct validity. Conclusion The SHL-SW is a reliable and valid instrument for assessing SHL among sex workers in Thailand, and is the first such instrument to be specifically validated for gender inclusivity in this population across four components: (1) access, (2) understanding, (3) appraisal, and (4) application. This tool enables public health practitioners and researchers to identify SHL gaps, design targeted rights-based interventions, and inform evidence-based policies aimed at advancing health equity.